Hybrid Adsorptive and Oxidative Removal of Natural Organic Matter Using Iron Oxide-Coated Pumice Particles - Sehnaz Sule Kaplan Bekaroglu; Nevzat Ozgu Yigit; Bilgehan Ilker Harman; Mehmet Kitis (Journal of Chemistry)
The aim of this work was to combine adsorptive and catalytic properties of iron oxide surfaces in a hybrid process using hydrogen peroxide and iron oxide-coated pumice particles to remove natural organic matter (NOM) in water. Experiments were conducted in batch, completely mixed reactors using various original and coated pumice particles. The results showed that both adsorption and catalytic oxidation mechanisms played role in the removal of NOM. The hybrid process was found to be effective in removing NOM from water having a wide range of specific UV absorbance values. Iron oxide surfaces preferentially adsorbed UV280-absorbing NOM fractions. Furthermore, the strong oxidants produced from reactions among iron oxide surfaces and hydrogen peroxide also preferentially oxidized UV280-absorbing NOM fractions. Preloading of iron oxide surfaces with NOM slightly reduced the further NOM removal performance of the hybrid process. Overall, the results suggested that the tested hybrid process may be effective for removal of NOM and control disinfection by-product formation.